Technical-tactical evolution of women`s football: a comparative analysis of ball possessions in the FIFA Women`s World Cup France 2019 and Australia & New Zealand 2023 - Iván-Baragaño, I.; Maneiro, R.; Losada, J. L.; Ardá, A. (Biology of Sport, 2025)
The aim of this study was to analyse and compare, both individually and multivariately, the technical-tactical similarities and differences associated with the offensive phase between the FIFA Women`s World Cup France 2019 and the FIFA Women`s World Cup Australia & New Zealand 2023. Following an observational follow-up design, 4,669 ball possessions were analysed in both tournaments (FWWC19: n = 2,323; FWWC23: n = 2,346). Differences between the two editions were examined using the chi-square statistic (p < .05) and Student`s t-test for categorical and continuous criteria, respectively. The effect size was calculated using the contingency coefficient and Cohen`s d, respectively. Lastly, a decision tree model was implemented with FWWC as the objective criterion. Statistically significant differences were found between the two tournaments for the criteria Match Status, Match Outcome, Defensive Intention, Interaction Context, MD, MO, Possession Time, and Passes. At the multivariate level, the predictor criteria introduced by the decision tree model were Match Status, Time, MO, Start Zone (width), Passes, Defensive Intention, and Possession zone. Between the two tournaments, increases in average possession time and the number of passes were observed, conditioned by greater technical and tactical efficiency of the teams. Similarly, in the latest edition, there was greater parity among the analysed teams, justifying the inclusion of more teams in the FWWC23. The results of this study demonstrate that in the last 4 years, elite women`s football has undergone a change characterized by ball possession and game control.